A low-temperature ZnO nanowire ethanol gas sensor prepared on plastic substrate. (2nd September 2016) - Lin, Chih-Hung; Chang, Shoou-Jinn; Hsueh, Ting-Jen
Abstract: In this work, a low-temperature ZnO nanowire ethanol gas sensor was prepared on plastic substrate. The operating temperature of the ZnO nanowire ethanol gas sensor was reduced to room temperature using ultraviolet illumination. The experimental results indicate a favorable sensor response at low temperature, with the best response at 60 °C. The results also reveal that the ZnO nanowire ethanol gas sensor can be easily integrated into portable products, whose waste heat can improve sensor response and achieve energy savings, while energy consumption can be further reduced by solar irradiation.